2007
DOI: 10.1051/forest:2007018
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected disproportion observed in species composition between oak mixed stands and their progeny populations

Abstract: -We used morphological analysis to assess species composition of natural regenerations and progeny plantations established from two mixed oak stands in Jamy and Legnica, Poland. Despite equal proportions of pedunculate (Quercus robur) and sessile oak (Quercus petrea) in seed stands, the species composition differed strikingly. In all progeny populations, pedunculate oak dominated, reaching 89.5% and 96.6% in Legnica and Jamy, respectively. However, sessile oak predominated in natural regenerations. Morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, the estimates were larger in this study than in many other studies of similar character. Dering and Lewandowski (2007) studied the species composition in two Polish mixed stands of Q. petraea and Q. robur and in seven plantations with material originating from these two stands. Natural regeneration in the stands was also assessed.…”
Section: Markersmentioning
confidence: 99%
“…Moreover, the estimates were larger in this study than in many other studies of similar character. Dering and Lewandowski (2007) studied the species composition in two Polish mixed stands of Q. petraea and Q. robur and in seven plantations with material originating from these two stands. Natural regeneration in the stands was also assessed.…”
Section: Markersmentioning
confidence: 99%
“…In practice, this can diminish the effect of hybridization. Dering and Lewandowski (2007) have demonstrated that species structure can be dramatically altered between Q. robur and Q. petraea depending on fitness and postzygotic selection of seeds and plants. Tendency towards closed forest canopy will promote survival of Q. petraea seedlings whereas large open forest gaps will promote the survival of Q. robur seedlings.…”
Section: Hybridizationmentioning
confidence: 99%